PENGARUH PEMBERIAN PIJAT OKSITOSIN TERHADAP PRODUKSI ASI PADA IBU POST SECTIO CAESAREA - Didiyunaspi, Didiyunaspi; Madetantra, Madetantra; Mawardi, Mawardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Childbirth is one of the normal physiological events experienced by a mother in the form of expelling the products of conception that live in the uterus through the vagina to the outside world. assistance or without assistance (own strength). The research design is a quasi-experimental method (Quasi Experimental) with the approach used in this research being a pre-post test design in one group (One-group pre-post test design). The characteristic of this type of research is that it reveals cause and effect relationship by involving one group of subjects. This research aims to determine the effect of giving oxytocin massage on breast milk production in mothers post Sectio Caesarea at Harapan Bunda Hospital, Batam. Frequency distribution before and after giving oxytocin massage at RSHB Batam City. Shows the results using the test Wilcoxon that the pretest and posttest have a mean rank value of 8.00 with a p-value of 0.0010.05 and it can be concluded that